Penegakan Hukum Pidana Terhadap Anggota Tni Yang Melakukan Tindak Pidana Desersi Di Wilayah Hukum Pengadilan Militer Iii-12 Surabaya (Studi Kasus Putusan Nomor 168-K/Pm.Iii-12/Al/Xii/2023) - Anggraini Esti Rahayu; Dudik Djaja Sidarta; Vallencia Nadya P; Hartoyo Hartoyo (Journal of Innovation Research and Knowledge, 2026)
This study aims to examine the enforcement of criminal law against Indonesian National Armed Forces (TNI) personnel who commit the offense of desertion within the jurisdiction of the Military Court III-12 Surabaya, with a case study of Decision Number 168-K/PM.III-12/AL/XII/2023. The research focuses on two main issues: the form of desertion committed and the legal considerations underlying the judge's decision in imposing criminal sanctions. This study employed a normative juridical method using both statutory and case approaches through the analysis of legislation, trial facts, and the ratio decidendi of the panel of judges. The findings indicate that the offense of desertion was committed in the form of unauthorized absence from military duty without valid permission from a superior for a period exceeding the legal limit during peacetime. Such conduct is regarded as a serious violation because it adversely affects military discipline, order, and the operational readiness of the unit. In rendering the judgment, the panel of judges considered the fulfillment of the elements of the criminal offense, the admissible evidence presented during the trial, and the absence of any justifying or excusing circumstances. The court also took into account both aggravating and mitigating factors relating to the defendant. The decision reflects the importance of balancing legal certainty, justice, and the objective of fostering military personnel to uphold their professional duties and responsibilities. Effective law enforcement is expected to create a deterrent effect while serving as a warning for other military personnel to comply with applicable military laws and regulations.